Indonesia's Contribution to The Development of International Climate Law (Judicial Analysis of The Implementation And Development of International Climate Law in The Riau Islands Province Region) - Hidayah, Luthfia; Shahrullah, Rina Shahriyani; Girsang, Junimart (Journal of Law and Policy Transformation, 2023)
The Indonesian state has made an important contribution to the development of international climate law by implementing efforts to reduce greenhouse gas emissions and protect environmental sustainability. By collaborating with other countries, Indonesia has also actively participated in negotiations on global agreements on climate change. Indonesia has also implemented regulations and programs for greenhouse gas emissions and deforestation, prioritizing ecosystems, which aim to improve ecosystem balance through sustainable forest and land management. Indonesia has pledged its commitment to overcoming climate change, remembering that Indonesia has peat soil and is rich in natural energy sources that can be used as renewable energy sources, developing renewable energy is a substitute for reducing fossil fuels that trigger greenhouse gas emissions. Indonesia has also developed an action concept aimed at reducing emission problems by up to 29% by 2030. RAN GRK is integrated through national agendas such as Nawacita and RAN (National Action Plan). In conducting research, the author uses normative legal research methods by accumulating information in the form of legal products. And with cooperation from developed countries as the largest contributors to gas emissions, developing countries should be able to collaborate well in carrying out efforts to develop international climate legislation.